Particle crushing and critical state surface of porous granular materials derived from artificial pumice - Itsuki Sato; Reiko Kuwano; Masahide Otsubo (Soils and Foundations)
Crushable porous soils, such as volcanic pumice, are distributed worldwide and cause a variety of engineering problems, such as slope hazards. The mechanical properties of these soils are complicated by their high compressibility due to voids in the particles themselves and changes in the soil gradation due to particle crushing. They are usually classified as problematic soils and discussed separately from ordinary granular soils, and their behaviour is not systematically understood. In this study, isotropic and triaxial compression tests were conducted on artificial pumice in order to determine the relationship between the mechanical properties and the particle crushing of crushable porous granular materials. The results showed that the mechanical behaviour of artificial pumice, representative of such materials, can be explained using a particle crushing index, which is related to the degree of efficient packing. Furthermore, a new critical state surface equation was proposed. It is applicable to crushable porous granular materials and shows the potential for expressing the critical state or isotropic consolidation state of such materials as a single surface in a three-dimensional space consisting of three axes: the stress − void ratio − crushing index. The validity of this new equation was confirmed by applying it to natural pumice from previous research.